The Impact of Waqf Investment Upon Welfare Society Based on Qur’anic Interpretation - Ahmad Fanani; Syarifah Nadhiya (Universitas Darussalam Gontor, 2022)
Waqf is one of several Islamic economic instruments that has a purpose to enhance welfare society and to support many worships are mentioned in verses of Qur’an. Focus on waqf for welfare society, almost many people defined that welfare is always talked about money and cash even though there are many things important could define welfare properly than just about cash on other hands, the study on the impact of waqf upon welfare society based on Qur’anic interpretation is still scant. This paper would like to discuss the impact of waqf upon welfare society based on Qur’anic interpretation on both sides are donors (waqif) and receivers (mauquf ‘alaih) that mentioned on surah An-Nahl 97 and al-Quraisy 1-4 used qualitative method by documentation and Tafseer interpretation approach. Lastly, the article concludes that waqf investment used integration of Islamic commercial and social finance could enhance welfare society which is related with a meaning of welfare based on Qur’anic interpretation like perpetual charity, serenity, and social soul for the donors and problem solving Islamic brotherhood, and economic growth for receivers.